Differences in receptive and productive vocabulary of an English and Arabic speaking bilingual girl - Alkurtehe M., Khaled Ali.; Rathakrishnan, Mohan; N. Krishnasamy, Hariharan (2019)
Objective of this study is to examine, assess, and describe sources of variations in a receptive and productive vocabulary of a bilingual child, who can speak English and Arabic. Dunn & Dunn’s Peabody Picture Vocabulary Test III (PPVT) (1997) was utilized to measure the productive and receptive vocabulary of 8 years old bilingual child. Findings of this study revealed that child’s performance in English was better than Arabic. She generated right vocabulary in English at 96 per cent, while it dropped to 67 per cent in Arabic.Receptive vocabulary of the child, however, was nearly equivalent in English and Arabic. This research showed that exposure to different frequency and context can cause differences in vocabulary size of a bilingual child.